Applicability of terahertz spectroscopy in dentistry: a scoping review - Da Silva, Carolina Pereira; Costa, Rayanna Thayse Florêncio; Pereira, Arthur Césare Messias Viana; Gomes, Jéssica Marcela de Luna [UNESP]; Gomes, Anderson Stevens Leônidas; Moraes, Sandra Lúcia Dantas; Lopes, Daniela Siqueira (Elsevier, 2024)
Objective: This study aimed to analyze the scope, nature, and extent of the applicability of terahertz (THz) spectroscopy in dentistry. Study Design: A scoping review was conducted following the 5-step methodology of Arksey and O'Malley, the PRISMA-ScR checklist, and the Evidence Synthesis Manual of the Joanna Briggs Institute. Electronic literature searches were performed in the PubMed/MEDLINE, Scopus, and Cochrane Library databases, including full-text articles with no specific publication period. The following research question was formulated: “What are the applications of THz spectroscopy in the field of dentistry?” Results: Seventeen laboratory studies were identified, detailing oral and dental applications of THz. In restorative dentistry, 8 investigations sought to identify the properties of human and animal dental tissues and differentiate between healthy and decayed tissue. In oral pathology, 5 articles analyzed the identification of cancer cells in comparison to the identification of these cells in histological or cytological analysis. In biomaterials, 4 papers studied the changes in properties of restorative materials and effects on polymerization. Conclusion: While the potential for early diagnosis using THz spectroscopy in dentistry is evident, our findings underscore its limitations. The studies were exclusively conducted in vitro, emphasizing the need for innovative clinical research using intraoral devices. Bridging this gap is essential to unlock the full potential of this noninvasive technology for early diagnosis and informed clinical decision-making.